IDENTIFIKASI TINGKAT PENGETAHUAN PENGUSAHA KECIL TERHADAP PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DI LINGKUNGAN KECAMATAN MEDAN LABUHAN - Liza Novietta; Ruswan Nurmadi (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2020)
The role of Micro, Small and Medium Enterprises (MSMEs) in the national economy in Indonesia is quite large. If MSME is managed and developed properly, it can create a strong MSME so that it can sustain the Indonesian economy. The condition of MSMEs as the backbone of the Indonesian economy can be seen in the 1997 monetary crisis, where many large companies went out of business and only MSMEs were able to survive. Accounting has an important role in the progress of MSMEs. This is due to the existence of good accounting records and in accordance with established accounting standards, it can help small businesses in making the right decisions, facilitate in obtaining credit from creditors and can provide accurate and timely information. By using financial statements as a basis for looking at the financial condition of a business, every decision taken by a business actor is based on real financial conditions. Seeing the importance of the level of knowledge of small entrepreneurs to the preparation of simple financial statements based on MSME Financial Accounting Standards in Indonesia, the researcher is interested in conducting a study entitled "Identification of the Level of Knowledge of Small Entrepreneurs on the Preparation of Simple Financial Statements Based on SAK-EMKM in the Medan Labuhan Sub-District Environment."